(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1994)
Living non-geniculate coralline algae were collected from 47 stations in the northern and central Tyrrhenian Sea (Tuscan Archipelago and Pontian Islands). Longitudinal sections of branches of Phymatolithon calcareum(Pallas) Adey & McKibbin show regular zonation, due to yearly cycles of growth. The alternating bands are generally thicker at shallower depth. A new morphology of Mesophyllum lichenoides (Ellis) Lemoine resulting from the adaptation to soft bottoms is described. The diagnostic elements of the vegetative thallus and the conceptacles of P. calcareum and M. lichenoides are described by biometry and Scanning Electron Microscope or Optical Microscope images. The geographic and bathymetric distribution of the two species is also given.